Unpredictable chronic prenatal stress and manifestation of generalized anxiety and panic in rat's offspring - Soliani, Flaviane Cristina de Brito Guzzo [UNESP]; Cabbia, Rafael [UNESP]; Kümpel, Vinícius Dias [UNESP]; Batistela, Matheus Fitipaldi [UNESP]; Almeida, Amarylis Garcia [UNESP]; Yamauchi Junior, Luiz [UNESP]; Andrade, Telma Gonçalves Carneiro Spera de [UNESP] (Elsevier, 2018)
Often the manifestation of anxiety cannot be explained by known environmental or hereditary factors. With this perspective, it has been reported that prenatal stress may lead to emotional disturbances in the offspring. However, studies relating prenatal stress to anxiety are controversial and generally the stressors used do not mimicks the reality experienced by mothers. Thus, this investigation evaluated the effects of an unpredictable chronic stress scheme applied in one of the three gestational weeks of rats on the manifestation of generalized anxiety and panic disorder in the progeny (males), analyzing, respectively, the avoidances and escapes in the elevated T-maze, at the 1st, 3rd or 6th month of progeny life. Control offspring showed increased generalized anxiety disorder and reduced panic at 6 months. The effects of prenatal stress depended on the gestational week where it occurred and on the progeny age: during the 1st gestational week the generalized anxiety decreased in 6 month old rats. Animals in the 3rd month, prenatally stressed during the last gestational week, showed anxiogenesis and panicogenesis, but effects reverted at the 6th month, when they presented anxiolysis and no changes related to panic. Together the results show that not only the gestational period in which the aversive experience occurred was important, but the age of the evaluated progeny, since the type and the intensity of behaviors related to anxiety may vary with the developmental stage. For the model of stress used in the present study, the effects of prenatal stress were more prominent when the exposure occurred during the 3rd gestational week in rats.
Keywords: Generalized anxiety disorder (GAD); Panic disorder (PD); Pregnancy; Prenatal stress; Unpredictable chronic stress